Postoperative acute parotitis after cesarean delivery under spinal anaesthesia: a rare entity - Shenoy, Kavitha V.; N., Usha; Srinivasan, T. R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Postoperative acute painless parotid gland swelling, which is a rare complication has been reported after caesarian section (CS) under neuraxial anaesthesia. Here, we present a parturient who suffered from acute parotitis, which developed after elective repeat CS under spinal anaesthesia.